Microwave synthesis and thermal properties of polyacrylate derivatives containing itaconic anhydride moieties - Osman Sameh M; El-Newehy Mohamed H; Al-Deyab Salem S; El-Faham Ayman (Chemistry Central Journal, 2012)
Abstract Background Microwave irradiation as an alternative heat source is now a well-known method in synthetic chemistry. Microwave heating has emerged as a powerful technique to promote a variety of chemical reactions, offering reduced pollution, low cost and offer high yields together with simplicity in processing and handling. On the other hand, copolymers containing both hydrophilic and hydrophobic segments are drawing considerable attention because of their possible use in biological systems. Various copolymer compositions can produce a very large number of different arrangements, producing materials of varying chemical and physical properties. Thus, the hydrophilicity of copolymers can be modified by changing the amount of incorporated itaconic anhydride. Results A series of methyl methacrylate (MMA) and acrylamide (AA) copolymers containing itaconic anhydride (ITA) were synthesized by microwave irradiation employing a multimode reactor (Synthos 3000 Aton Paar, GmbH, 1400 W maximum magnetron) as well as conventional method. The thermal properties of the copolymers were evaluated by different techniques. Structure-thermal property correlation based on changing the itaconic anhydride ratio was demonstrated. Results revealed that the incorporation of itaconic anhydride into the polymeric backbone of all series affect the thermal stability of copolymers. In addition, the use of the microwave method offers high molecular weight copolymers which lead eventually to an increase in thermal stability. Conclusions Microwave irradiation method showed advantages for the produced copolymers compared to that prepared by conventional method, where it can offer a copolymer in short time, high yield, more pure compounds and more thermally stable copolymers, rather than conventional method. Also, microwave irradiation method gives higher molecular weight due to prevention of the chain transfer. Moreover, as the itaconic anhydride content increases the thermal stability and Tg increase due to the decrease in the crystallinity.